Elucidating the Evolutionary Relationships among Bos taurus Digestive Organs Using Unigene Expression Data. (8th February 2010) - Beck, D. C.; Jiang, Honglin; Zhang, Liqing
Abstract : Although the nature of ruminant evolution is still disputed, current theory based on physiology and genetic analysis suggests that the abomasum is the evolutionarily oldest stomach compartment, the rumen evolved some time after the abomasum, and the omasum is the evolutionarily youngest stomach compartment. In addition, there is some evidence of relaxed selective constraint in the stomach-like organ and the foregut shortly after the foregut formation event. Along with the assumption of a mean, stochastic rate of evolution, analysis of differences in genetic profiles among digestive body organs can give clues to the relationships among these organs. The presence of large numbers of uniquely expressed entries in the abomasum and rumen indicates either a period of relaxed selective constraint or greater evolutionary age. Additionally, differences in expression profiles indicate that the abomasum, rumen, and intestine are more closely related to each other, while the reticulum and omasum are more closely related to the rumen. Functional analysis using Gene Ontology (GO) categories also supports the proposed evolutionary relationships by identifying shared functions, such as muscle activity and development, lipid transport, and urea metabolism, between all sections of the digestive tract investigated.